Automated Attendance System Using Facial Recognition (International Journal of Scientific Research in Science and Technology, 2024)
In contemporary educational and organizational settings, efficiently tracking attendance remains a significant challenge. Manual methods are prone to errors and time-consuming. To address these challenges, this study proposes an Automated Attendance System (AAS) utilizing Facial Recognition technology. The system leverages state-of-the-art techniques in image processing and machine learning to accurately identify individuals and record their attendance seamlessly. The AAS operates through a multi-step process. Initially, a comprehensive dataset is compiled comprising facial images of registered individuals. This dataset serves as the reference for subsequent recognition tasks. Upon input of an image, the system employs advanced algorithms for facial detection and matching, such as Histogram of Oriented Gradients (HOG), to identify individuals in real-time.Key to the system’s functionality is its integration with Raspberry Pi, a versatile microcontroller, which serves as the hardware backbone. Raspberry Pi facilitates efficient processing of image data and enables real-time analysis, ensuring rapid attendance tracking. Additionally, the system incorporates an LCD display to provide immediate feedback, enhancing user experience and facilitating interaction. Furthermore, upon successful identification, attendance records are automatically updated in a centralized Excel spreadsheet, ensuring easy access and management of attendance data. This integration streamlines administrative tasks and enhances the overall efficiency of attendance tracking. Moreover, the system is equipped with a mailing feature, enabling administrators to receive notifications and reports regarding attendance status periodically. This feature ensures seamless communication and enhances the system’s adaptability to diverse organizational environments.